A ABORDAGEM DA TEMÁTICA DA ELETRICIDADE NO ENSINO DE FÍSICA ATRAVÉS DA APRENDIZAGEM BASEADA EM PROJETOS: POSSIBILIDADES E DESAFIOS NO DESENVOLVIMENTO DE DIFERENTES TIPOS DE CONTEÚDO. - Souza, Thays Ferreira (2021)
With the development of contemporary society, several changes have occurred in the ways of life and work, however these changes are not always inserted into formal education institutions. There is an increasing tendency for an improvement of knowledge in